2017
DOI: 10.1002/smj.2648
|View full text |Cite
|
Sign up to set email alerts
|

Is there a “Dark Side” to Monitoring? Board and Shareholder Monitoring Effects on M&A Performance Extremeness

Abstract: Research summary: We investigate the effects of monitoring by boards of directors and institutional shareholders on merger and acquisition (M&A) performance extremeness using a sample of M&A deals from 1997 to 2006. Both governance research and legal reforms generally have espoused a “raise all boats” view of monitoring. We instead investigate whether monitoring may serve as a double‐edged sword that limits CEO discretion to undertake both value‐destroying M&A deals and value‐creating ones. Our findings indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 91 publications
2
45
0
Order By: Relevance
“…Furthermore, following previous studies in management (Goranova, Priem, Ndofor, & Trahms, ), we consider different types of institutional investors. Following Bushee () and Goranova et al (), institutional investors are classified into three groups: (a) transient institutional investors holding diversified portfolios with high turnover, (b) dedicated institutional investors holding concentrated portfolios with low turnover, and (c) quasi‐indexer institutional investors holding diversified portfolios with low turnover. Information on this classification is obtained from Bushee's website and three variables are constructed for the institution types .…”
Section: Empirical Design and Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, following previous studies in management (Goranova, Priem, Ndofor, & Trahms, ), we consider different types of institutional investors. Following Bushee () and Goranova et al (), institutional investors are classified into three groups: (a) transient institutional investors holding diversified portfolios with high turnover, (b) dedicated institutional investors holding concentrated portfolios with low turnover, and (c) quasi‐indexer institutional investors holding diversified portfolios with low turnover. Information on this classification is obtained from Bushee's website and three variables are constructed for the institution types .…”
Section: Empirical Design and Resultssupporting
confidence: 92%
“…While the moderated effect got weaker when either type of option was solely used, the results remain largely consistent and support Hypothesis 2. Furthermore, following previous studies in management (Goranova, Priem, Ndofor, & Trahms, 2017), we consider different types of institutional investors. Following Bushee (1998) and Goranova et al (2017), institutional investors are classified into three groups: (a) transient institutional investors holding diversified portfolios with high turnover, (b) dedicated institutional investors holding concentrated portfolios with low turnover, and (c) quasi-indexer institutional investors holding diversified portfolios with low turnover.…”
mentioning
confidence: 99%
“…First, the literature on interlocks [21,28], on former politicians on boards [25,30,33], and on acquisitions has generally been addressed separately. The literature on corporate governance has suggested that the use of board interlocks may be a corporate board mechanism used to gain access to other companies [3] and to obtain more accurate information [107], which improves firm performance [6]. Former politicians not only possess unique knowledge of the practices of various regulators, but they also make the acquisition processes more attractive to the company [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, consideration of acquisition sins also risks research on human shortcomings legitimizing them (Ghoshal 2005), and good intentions of counteracting sins may play out in complex ways. For instance, excessive control may actually counteract reaching strategic goals as performance of intrinsically motivated may punish principals when they perceive excessive control as signs of lack of trust, or greed (Falk and Kosfeld 2006;Goranova et al 2017). While this must be taken seriously and a paradigmatic neglect of self-interest may leave acquisition theory unable to understand certain behaviors, we also believe there are benefits to address more positive human traits, and we hope our study can inspire more research along the lines outlined here.…”
Section: Conclusion and Future Researchmentioning
confidence: 92%